2015
DOI: 10.1016/j.oraloncology.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intensity-modulated radiotherapy on nasopharyngeal carcinoma: Validation of the 7th edition AJCC staging system

Abstract: When treated with IMRT, the difference in the LRFS, DSS, and OS between T1 and T2 patients diminished, indicating that it is rational to merge T2 into T1. The prognostic value of the N classification of the current staging system had not changed much compared to the 6th edition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 26 publications
(33 reference statements)
2
57
0
Order By: Relevance
“…Based on MRI and IMRT, no systematic data referring to prognostic factors in patients with NPC were available. Zong et al [24] focused on skull base extension and found that it did not influence local failure in the IMRT era. Based on the same database presented here, our previous studies reported that skull base extension [25] and parapharyngeal tumor extension [26] were not independent prognostic factors for local control in patients with NPC treated with IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…Based on MRI and IMRT, no systematic data referring to prognostic factors in patients with NPC were available. Zong et al [24] focused on skull base extension and found that it did not influence local failure in the IMRT era. Based on the same database presented here, our previous studies reported that skull base extension [25] and parapharyngeal tumor extension [26] were not independent prognostic factors for local control in patients with NPC treated with IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy, with IMRT as the lead therapy, has dramatically improved the prognosis of NPC patients and the 5-year overall survival has reached 80% [6][7][8][9][10][11][12]. Zong et al [23] surveyed 1241 nasopharyngeal carcinoma (NPC) patients treated with IMRT, of whom 88.7% of patients received concurrent platinum-based chemotherapy. The 5-year rates of OS, DSS, DMFS, RRFS and LRFS were 81.1%, 82.6%, 82.6%, 95.4%, and 92.9% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Chen et al’s [4] and Zong et al’s [7] trials, there were no significant differences in DMFS between the N2 and N3a categories when using the 7 th edition AJCC staging system. Thus, it might be feasible to downstage N3 to N2 in both staging systems.…”
Section: Discussionmentioning
confidence: 99%